YjbH regulates virulence genes expression and oxidative stress resistance in Staphylococcus aureus. Issue 1 (31st December 2021) - Paudel, Atmika; Panthee, Suresh; Hamamoto, Hiroshi; Grunert, Tom; Sekimizu, Kazuhisa
ABSTRACT: We previously reported that disruption of the yjbI gene reduced virulence of Staphylococcus aureus . In this study, we found virulence in both silkworms and mice was restored by introducing the yjbH gene but not the yjbI gene to both yjbI and yjbH genes-disrupted mutants, suggesting that yjbH, the gene downstream to the yjbI gene in a two-gene operon- yjbIH, is responsible for this phenomenon. We further observed a decrease in various surface-associated proteins and changes in cell envelope glycostructures in the mutants. RNA-seq analysis revealed that disruption of the yjbI and the yjbH genes resulted in differential expression of a broad range of genes, notably, significant downregulation of genes involved in virulence and oxidative stress. Administration of N-acetyl-L-cysteine, a free-radical scavenger, restored the virulence in both the mutants. Our findings suggested that YjbH plays a role in staphylococcal pathogenicity by regulating virulence gene expression, affecting the bacterial surface structure, and conferring resistance to oxidative stress in a host.